Borders of (in)finiteness : Tundra Nenets predication in change - Jalava, Lotta (Helsingin yliopisto, 2015)
The dissertation consists of four academic articles and an introductory chapter explaining the objectives, background and results of the study. It concentrates on the variation and change in predicate structures in Tundra Nenets, a Samoyedic (Uralic) language spoken in Siberia. The focus of the study is on the finite and non-finite forms and the concept of finiteness in grammatical change. The study investigates those grammatical categories that show variation in verbal and non-verbal predication or that are results of grammaticalization processes that include changes in non-finite verb forms. The topics of the articles are adjectival words, modal and evidential categories, and the essive-translative constructions in Tundra Nenets. The data consists of published texts in Tundra Nenets from different periods of time representing different genres, as well as fieldwork material recorded on the Taimyr Peninsula in 2011. The approach is functional typological, and the methodology combines synchronic linguistic description and diachronic explanation of the grammatical phenomena. The linguistic processes are analysed with relation to language use and context, and their development is explained with relation to the synchronic variation in the language and similar structural and functional paths of change in other languages. The findings of this study complement earlier research by suggesting mechanisms and paths of change for categories whose origin has been hypothesized in earlier studies. The results suggest that non-finite verb forms often serve as a basis for modal and evidential verb forms in Tundra Nenets, but they can also take part in grammaticalization processes that produce nominal categories, such as the essive-translative suffix. At the same time, the study provides syntactic analyses of lesser studied grammatical categories in Tundra Nenets. It also contributes to the more general discussion on finiteness and infiniteness as well as the division of main word classes in grammatical change. ...